2011
DOI: 10.1111/j.1463-1326.2011.01359.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and pharmacodynamics of dapagliflozin, a novel selective inhibitor of sodium-glucose co-transporter type 2, in Japanese subjects without and with type 2 diabetes mellitus

Abstract: Dapagliflozin was well tolerated and showed predictable dose-proportional PK and PD parameters in both healthy and T2DM Japanese subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
92
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(112 citation statements)
references
References 13 publications
18
92
0
Order By: Relevance
“…The mouse data are similar to both our F-Dapa (not shown) and the [ 14 C] dapagliflozin results in human subjects. 17 After displacing F-Dapa from the kidney, we observed a transient increase in the concentration of F-Dapa in plasma, especially in the renal vein ( Figure 5B). This along with the lack of F-Dapa binding in the renal medulla ( Figure 6) indicate that F-Dapa is reabsorbed by nephrons back into blood.…”
Section: F-dapa Excretion and Metabolismmentioning
confidence: 90%
See 1 more Smart Citation
“…The mouse data are similar to both our F-Dapa (not shown) and the [ 14 C] dapagliflozin results in human subjects. 17 After displacing F-Dapa from the kidney, we observed a transient increase in the concentration of F-Dapa in plasma, especially in the renal vein ( Figure 5B). This along with the lack of F-Dapa binding in the renal medulla ( Figure 6) indicate that F-Dapa is reabsorbed by nephrons back into blood.…”
Section: F-dapa Excretion and Metabolismmentioning
confidence: 90%
“…The identity of the 18 F metabolites in plasma and urine has not yet been determined, but the major band in mouse plasma and urine may be F-dapagliflozin-3-O-glucuronide, the major metabolite found in human plasma and urine. 17 Finally, 97% of the activity extracted from rat kidney was F-Dapa.…”
Section: Metabolites Of F-dapamentioning
confidence: 99%
“…Several SGLT2-selective inhibitors are in various stages of clinical trials (Aires and Calado, 2010;Nair and Wilding, 2010;Sha et al, 2011); proof-of-concept has been reported with dapagliflozin (Meng et al, 2008) in phase 2b studies in patients with type 2 diabetes Kasichayanula et al, 2011). Results from a 24-week phase 3 clinical study with dapagliflozin have also demonstrated significant mean reductions in the primary endpoint, glycosylated hemoglobin levels and in the secondary endpoint, fasting plasma glucose, when added to metformin in people with T2DM inadequately controlled with metformin alone (Bailey et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The best sensitivity obtained in those assays was 1 ng/mL in plasma with a plasma volume of 150-”L 14,15 or 0.1 ng/mL with a plasma volume of 500-”L using LC-MS/MS detection with an API-5000 mass spectrometer 17 . Basic pH mobile phases were used in these two assays 14,15,16 .…”
Section: Historical Assay Challengesmentioning
confidence: 99%